Simultaneous Estimation Of Ambroxol Hydrochloride And Loratadine In Tablet Dosage Form By Using UV Spectrophotometric Method - ILANGOVAN PONNILAVARASAN; CHEBROLU.SUNIL NARENDRA KUMAR; P.ASHA (International Journal of Pharma and Bio Sciences, 2011)
A novel, simple, rapid, precise, accurate, cost effective and reproducible spectrophotometric method has been developed for simultaneous estimation of ambroxol hcl and loratadine in combined tablet dosage form. The method employs measurement of absorbance at two wavelengths,308nm and 245nm, of ambroxol and loratadine respectively. Beer´s law obeyed in the concentration range of 10-50µg/ml and 10-50µg/ml for ambroxol and loratadine respectively.. The proposed method is recommended for routine analysis since it is rapid, simple, accurate, and also sensitive and specific. Results of percentage recovery studies confirmed the accuracy of the proposed method. The present uv spectroscopic method was validated following the ICH guidelines17-18.